2005
DOI: 10.1179/174329305x68750
|View full text |Cite
|
Sign up to set email alerts
|

Effects of torch configuration and welding current on weld bead formation in high speed tandem pulsed gas metal arc welding of steel sheets

Abstract: Undercut and humping bead are the common defects that limit the maximum welding speed of tandem pulsed gas metal arc (GMA) welding. In order to increase the maximum welding speed, effects of the inclination angle, interwire distance and welding current ratio between the leading wire and trailing wire on bead formation in high speed welding are investigated. The undercut and humping bead is attributed to the irregular flow of molten metal towards the rear part of the weld pool. This irregular flow can be preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(47 citation statements)
references
References 8 publications
0
39
0
3
Order By: Relevance
“…However, there are the following problems in the practical field of welding. Automation of the welding with high efficiency and a high quality are required due to the globalization of the field of manufacturing, and the decrease of the welding engineer 1) . In the CO 2 welding, spatter and fume occur.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are the following problems in the practical field of welding. Automation of the welding with high efficiency and a high quality are required due to the globalization of the field of manufacturing, and the decrease of the welding engineer 1) . In the CO 2 welding, spatter and fume occur.…”
Section: Introductionmentioning
confidence: 99%
“…Taking gas metal arc welding (GMAW), for example, a great deal of research efforts that are mainly in respect of multi-wire arc welding equipped with single or several welding power sources were carried out [2][3][4]. Corresponding welding technologies were developed, e.g., tandem twin-wire welding [5][6][7], consumable doubleelectrode GMA welding [8][9][10][11], hybrid laser double GMA welding [12][13][14], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that the resistance to arc extinction was increased as the arcing current was also increased. For now, some prevalent methods to reduce the arc interference are listed as follows: (1) adjusting the distance between welding wires and the angle of welding torch [4], (2) adjusting the ratio of gas and current [5], and (3) using pulse coordination control [6].…”
Section: Introductionmentioning
confidence: 99%